The regional effects of CO2 and landscape change using a coupled plant and meteorological model - Eastman, Joseph L.; Coughenour, Michael B.; Pielke, Roger A. (Global change biology, 2001)
A meteorological model, the Regional Atmospheric Modelling System (RAMS), and a plant model, the General Energy and Mass Transfer Model (GEMTM), are coupled in this study. The integrated modelling system was used to investigate regional weather conditions in the central grasslands of the USA for three experimental scenarios: • land cover is changed from current to potential vegetation; • radiative forcing is changed from 1 × CO2 to 2 × CO2; and • biological CO2 partial pressures are doubled. Results indicate that the biological effect of enriched CO2, and of land‐use change exhibit dominant effects on regional meteorological and biological fields, which were observed for daily to seasonal time scales and grid to regional spatial scales. Simulated radiation impacts of 2 × CO2 were minimal, with interactive effects between the three experimental scenarios as large as the radiational impact alone. Model results highlight the importance of including 2 × CO2 biological effects when simulating possible future changes in regional weather.